DNA variants are an unlikely explanation for the changing quality of spermatozoa within the same individual. (20th October 2021) - Netherton, Jacob; Ogle, Rachel; Hetherington, Louise; Velkov, Tony; Rose, Ryan; Baker, Mark
Abstract: It has recently been suggested that the human sperm genome is highly unstable, which may be a reasonable explanation as to why men, even fertile men, produce defective spermatozoa. Furthermore, an unstable genome may also explain why the semen profile of the same man changes from one ejaculate to the next. As such, we took multiple ejaculates (between 3 and 6) from 7 individuals over a 6-month period and isolated sperm through density gradients. We then compared the DNA of: (i) good and poor-quality spermatozoa within the same ejaculate; and (ii) from multiple ejaculates from the same individual. Our results suggest that on a global level, DNA present within spermatozoa is actually quite stable and similar between both good and poor sperm. This is important information for the assisted reproductive community when it comes to sperm selection.